2013
DOI: 10.1177/1742395313475674
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes self-management in a low-income population: impacts of social support and relationships with the health care system

Abstract: Objectives This article reports on results of a qualitative study of social supports and institutional resources utilized by individuals living with diabetes in a high-poverty urban setting. The goal was to examine how access to social capital among low-income populations facilitates and impedes their self-efficacy in diabetes self-management. Methods Semi-structured interviews were conducted with 34 patients with diabetes from a safety net primary care practice in Buffalo, New York. Results Facilitators a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 23 publications
2
92
0
2
Order By: Relevance
“…The definitions of social support (Table 1) convey the need for a uniform description of the attributes that delineate the concept. In their concept analysis of social support, Langford et al (1997) Appraisal support is an intangible support that positively reinforces changes in patient behavior in following predetermined self-management guidelines (Vest et al, 2013).…”
Section: Conceptual Definitions Of Social Supportmentioning
confidence: 99%
See 4 more Smart Citations
“…The definitions of social support (Table 1) convey the need for a uniform description of the attributes that delineate the concept. In their concept analysis of social support, Langford et al (1997) Appraisal support is an intangible support that positively reinforces changes in patient behavior in following predetermined self-management guidelines (Vest et al, 2013).…”
Section: Conceptual Definitions Of Social Supportmentioning
confidence: 99%
“…In addition, personal variables such as gender, culture, and race of both the support person and the patient were important variables that strengthen or hinder social support (Cosansu & Erdogan, 2013;Hempler et al, 2013;Mathew et al, 2012;Strom & Egede, 2012;Venkatesh & Weatherspoon, 2013;Vest et al, 2013). For example, Strom and Egede (2012) found that racial differences had a great impact on the mode of delivery of social support.…”
Section: Conceptual Definitions Of Social Supportmentioning
confidence: 99%
See 3 more Smart Citations